PENGARUH MOTIVASI DAN PERSEPSI TERHADAP MINAT MAHASISWA MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI (PPAK) DI KOTA SEMARANG - fajarsari, hesti (Universitas Muhammadiyah Tangerang, 2020)
This study investigates the effect of motivation (quality, career, economic and social) and perception (the cost of education and study duration) on students' interest in taking PPAk. The variables used are quality motivation, career motivation, economic motivation, social motivation, perception of education costs and perception of study duration as independent variables, and student interest in accepting PPAk as the dependent variable. The study used a questionnaire with a total sample of 73 people. The analysis tool uses multiple linear regression.The results showed that quality motivation, career motivation, economic motivation, social motivation, perception of educational costs and perception of study duration simultaneously had a significant effect on the interest of accounting students following the PPAk. The value of the regression model obtained by 0.356, which means that 35.6% of students' interest in participating in PPAk can be explained by the 6 variables. However, based on a partial analysis, only career motivation and social motivation have a significant positive effect on the interest of accounting students of PPA studies in the city of Semarang. While other variables such as quality motivation, economic motivation, perceptions of educational costs and perception of study duration did not affect the interest of accounting students in taking PPAk in the city of Semarang.